Curriculum Development for Arabic Language Enhancement Through Muntada Lughah in Modern Pesantren - Fairuz Subakir; Agus Yasin; Siti Nikmatul Rochma; Nur Fera Khalifah; Nuraeni Rahmawati (Education and Sociedad Journal, 2025)
This study aims to analyze curriculum development for Arabic language enhancement through Muntada Lughah at Pondok Modern. The research employed a qualitative case study approach involving language supervisors, Arabic teachers, curriculum coordinators, student committees, and fifth-grade students of Kulliyyatu-l-Mu’allimat al-Islamiyyah (KMI). Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that Muntada Lughah functions as a curriculum enrichment program integrating communicative language learning, immersive language environments, and leadership-oriented educational practices. The program was implemented through seminars, public speaking training, discussion forums, listening practices, grammar reinforcement, and language correction sessions that encouraged active Arabic communication among students. The study further demonstrates that the program contributed not only to improving Arabic proficiency but also to strengthening students’ self-confidence, discipline, teamwork, and leadership character through hidden curriculum practices embedded within pesantren culture. In addition, the findings indicate that curriculum development in modern pesantren requires authentic interaction, institutional language environments, and participatory learning experiences beyond conventional classroom instruction. This study contributes theoretically to Arabic curriculum development discourse and practically offers an alternative model for communicative and leadership-based language learning in Islamic boarding schools.